Kinerja di Sektor Perhotelan: Peran Kepemimpinan Transformasional pada Karyawan - Untung La Paudi (Universitas 45 Surabaya, 2025)
Employee performance and transformational leadership are the central focus of this study, which seeks to examine the extent to which leadership style influences employees’ work outcomes. The research involved a sample of 68 participants drawn from the organization under study. Data were collected using structured questionnaires to minimize interpretation bias and ensure consistency between respondents’ perceptions and the researchers’ measurements. The collected data were then processed and analyzed using SPSS version 26 as the primary statistical analysis tool. The results of the hypothesis testing indicate that transformational leadership has a significant effect on employee performance. This is evidenced by the t-test results, where the calculated t-value for the transformational leadership variable (9.458) exceeded the t-table value (1.997), and the significance level obtained was 0.00, which is lower than the predetermined alpha value. These findings demonstrate that transformational leadership positively and significantly influences employee performance, suggesting that leaders who inspire, motivate, and support employees can effectively enhance productivity, work quality, and overall organizational performance.